Kirk-Othmer Encyclopedia of Chemical Technology 2008
DOI: 10.1002/0471238961.ozonzaik.a01
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Applications

Abstract: Ozone applications are based on the powerful oxidative action of ozone. The ozonolysis of chemical and biochemical compounds, as a rule, takes place with high rates at low temperatures and activation energies. This result provides a basis for the development of novel and improved technologies, which find wide application in ecology, chemical, pharmaceutical, cosmetics, cellulose, paper and sugar industries, microelectronics, and many others. This article focuses on technologies for purification of waste gases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Step 2 is considered to be a very important reaction to produce four diastereomers on the cabbage leaf surface, in which the four patterns of nonhomologous random recombination of carbonyl oxide ions and carbonyl compounds produced from the primary ozonide may be deeply involved. Incidentally, the secondary ozonides are considered to be less toxic to mammals because they are highly likely to be unstable in mammalian tissue due to their rapid decomposition in aqueous solutions. Furthermore, an ozonide derivative of unsaturated lipid, methyl oleate, was orally administered to rats, which resulted in low toxicity, probably due to its fast degradation by enzymes and biological antioxidants such as glutathione transferase and vitamins, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Step 2 is considered to be a very important reaction to produce four diastereomers on the cabbage leaf surface, in which the four patterns of nonhomologous random recombination of carbonyl oxide ions and carbonyl compounds produced from the primary ozonide may be deeply involved. Incidentally, the secondary ozonides are considered to be less toxic to mammals because they are highly likely to be unstable in mammalian tissue due to their rapid decomposition in aqueous solutions. Furthermore, an ozonide derivative of unsaturated lipid, methyl oleate, was orally administered to rats, which resulted in low toxicity, probably due to its fast degradation by enzymes and biological antioxidants such as glutathione transferase and vitamins, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Studies of anthropogenic and biogenic alkene ozonolysis in the atmosphere have concluded that these reactions have a complex impact on air pollution and the overall composition of the atmosphere. Many of these studies cite the need for a more complete understanding of the mechanism of the ozone–alkene reaction. The reaction mechanism first proposed by Criegee in 1949 , is widely accepted ,, on the basis of considerable indirect experimental evidence and theoretical calculations. This mechanism begins with the formation of an initial primary ozonide through addition of the ozone across the double bond followed by C–C and O–O bond rupture to form a Criegee intermediate and a carbonyl-containing species. However, other mechanisms have been proposed .…”
Section: Introductionmentioning
confidence: 99%